2017
DOI: 10.1136/bjsports-2017-098001
|View full text |Cite
|
Sign up to set email alerts
|

Is there a correlation between coaches’ leadership styles and injuries in elite football teams? A study of 36 elite teams in 17 countries

Abstract: BackgroundDo coaches’ leadership styles affect injury rates and the availability of players in professional football? Certain types of leadership behaviour may cause stress and have a negative impact on players’ health and well-being.AimTo investigate the transformational leadership styles of head coaches in elite men’s football and to evaluate the correlation between leadership styles, injury rates and players’ availability.MethodsMedical staff from 36 elite football clubs in 17 European countries produced 77… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(84 citation statements)
references
References 35 publications
5
77
0
2
Order By: Relevance
“…Reviews of sport injury prevention studies underline the inadequate use of theory-based methods to increase the effectiveness of such behavior change interventions. 33,39 To conclude, the findings of our study, and similar results reported by others, 1,[33][34][35][36][37]39 indicate that psychological components may constitute an important part of injury prevention training for youth handball players.…”
Section: Discussion With Key Representativessupporting
confidence: 86%
See 1 more Smart Citation
“…Reviews of sport injury prevention studies underline the inadequate use of theory-based methods to increase the effectiveness of such behavior change interventions. 33,39 To conclude, the findings of our study, and similar results reported by others, 1,[33][34][35][36][37]39 indicate that psychological components may constitute an important part of injury prevention training for youth handball players.…”
Section: Discussion With Key Representativessupporting
confidence: 86%
“…The way in which coaches communicate with players appears to play a role here. Recent studies have reported that a democratic leadership style (involving motivating and inspiring players) is related to a lower incidence of severe injuries among male soccer players, 36 and that strong coach feedback results in worse game performance than mild, unobtrusive coach feedback in youth soccer players. 37 In addition, Go-zone statements 11 and 71 underline the long-term benefits of preventing sport-related injuries, and highlight the importance of maintaining injury prevention training over time.…”
Section: Discussion With Key Representativesmentioning
confidence: 99%
“…The creation of injury prevention programmes during this timeframe has aimed to reduce injury incidence. However, training programmes, such as the FIFA 11+ are not enforced or used consistently (Bahr, Thorborg, & Ekstrand, 2015), with differences in training philosophies and coaches leadership styles at individual clubs often dictating the loading and injury prevention schedule, leading to a subsequent variance in injury incidence (Ekstrand, 2016;Ekstrand et al, 2017;Malone et al, 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Therefore, football staff should consider looking at current practices around suggested risk factors such as coaching philosophy, previous injury and load management (Ekstrand et al, 2017;Hägglund et al, 2006;Malone et al, 2017), in order to reduce the incidence and prevalence of injury over subsequent seasons.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…MSS susceptibility to injuries may change as a result of bottom-up (from subcellular or cellular level to the MSS level) and top-down influences of constraints (from social and psychological levels to the MSS level), recently reported through the association found between coaches' leadership style and injury rates. 64 The effects of fear, anxiety, stress, motivation and emotional arousal on motor coordination, 14 65 66 often disregarded in some models of sports injury, should also be taken into account due to their longterm effects on MSS.…”
Section: Top-down Effects On Mss Susceptibilitymentioning
confidence: 99%